Influência da obesidade-MSG e doença periodontal materna induzida sobre a perda óssea alveolar da prole masculina na vida adulta - Paula, Thayná Náthally Petry de (2020)
Objective: To verify the influence of obesity induced by neonatal treatment with monosodium glutamate (MSG) and maternal periodontal disease on the mandibular bone loss of male offspring in adulthood. Materials and methods: Twenty neonatal Wistar females were used and randomly separated into two groups. During the first five days of life, half of the female pups received subcutaneous injections in the cervical region of 4g/kg/day of monosodium glutamate (MSG group, n = 30), and the other half received 1.25/kg/day of hyperosmotic saline solution. (CTRL group, n = 30). All animals used in the experiments received water and standard feed throughout the experimental period. At 70 days of life, 15 animals from each group were submitted to periodontal disease and distributed into four experimental groups: control with no ligature (CTRL NL), control with a ligature (CTRL WL), MSG with no ligature (MSG NL), and MSG with a ligature (MSG WL). The four groups of females reproduced with control rats (2:1 ratio). Offspring were classified into four groups, according to the mothers' treatment: CTRL NL-F1, CTRL WL-F1, MSG NL-F1, and MSG WL-F1. At 120 days of age, the offspring were euthanized. Hemimandibles were collected for histological, morphological, and radiographic analysis and a portion of gingival tissue for analysis by enzyme-linked immunosorbent assay (ELISA) of cytokines IL-6, IL-10, IL-17, and TNF-alpha. Data were assessed using Two-way ANOVA and Tukey's test. Results: There were no changes related to maternal hypothalamic obesity associated with periodontal disease in alveolar bone loss in the male offspring of F1 rats at 120 days. Conclusion: Hypothalamic obesity and maternal periodontal disease did not affect the body and plasma parameters of their male offspring in the first generation, demonstrating that there was no effect of fetal programming on these parameters.